The TGF-β Family: Signaling Pathways, Developmental Roles, and Tumor Suppressor Activities - Aaron N. Johnson; Stuart J. Newfeld (The Scientific World Journal)
Intercellular communication is a critical process for all multicellular organisms, and communication among cells is required for proper embryonic development and adult physiology. Members of the Transforming Growth Factor-β (TGF-β) family of secreted proteins communicate information between cells via a complex signaling pathway, and family members are capable of inducing a wide range of cellular responses. The purpose of this review is to provide the reader with a broad introduction to our current understanding of three aspects of the TGF-β family. These are the molecular mechanisms utilized by TGF-β signaling pathways, the developmental roles played by TGF-β family members in a variety of species, and the growing list of cancers in which various TGF-β signaling pathways display tumor suppressor activity.